(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
In order to predict postoperative complications of acute intestinal obstruction in elderly and senile patients, it is recommended to study such blood parameters as markers of the inflammatory response, indicators of the rate of thrombus formation and endothelial dysfunction.